Modelling and Implementation of Complex Systems Proceedings of the 4th International Symposium, MISC 2016, Constantine, Algeria, May 7-8, 2016, Constantine, Algeria - Chikhi, Salim; Amine, Abdelmalek; Chaoui, Allaoua; Kholladi, Mohamed Khireddine; Saidouni, Djamel Eddine (Lecture Notes in Networks and Systems, 2016)
This volume is a comprehensive collection of extended contributions from the fourth international symposium on Modeling and Implementing Complex Systems (MICS'2106) organized into four main topics: Networking and Cloud Computing, Software Engineering and Formal Methods, Intelligent and Information Systems, and Algorithms and Complexity. This book presents recent advances related to theory and applications of networking and distributed computing, including: cloud computing, software engineering, formal methods, information extraction, optimization algorithms, intelligent systems, and multi-agent systems.